The Radical Group in Context: 1. An Integrated Framework for the Analysis of Group Risk for Terrorism - Post, Jerrold M.; Ruby, Keven G.; Shaw, Eric D. (Studies in conflict and terrorism, 2002)
On the basis of a systematic expert knowledge acquisition process, a framework has been developed that takes into account critical variables--internal and external, as well as interactions between them and the group under examination--that are understood to increase risk for escalation toward political violence. The indicators identified are grouped within four conceptual categories: (1) External factors, including historical, cultural, and contextual features; (2) Key actors affecting the group, including the regime and other opponents, as well as Constituents and Supporters; (3) The Group/Organization: Characteristics, Processes, and Structures, including an examination of such factors as leadership style and decision making, group experience with violence, and group ideology and goals; and (4) Characteristics of the Immediate Situation, including Triggering Events. A total of 32 variables were identified within the 4 categories to establish the overall integrated framework. This framework provides the basis for the rigorous analysis of a radical group's risk for terrorism.